Boronic acid inhibitors of penicillin-binding protein 1b: serine and lysine labelling agents - Levente Kollár; Katarina Grabrijan; Martina Hrast Rambaher; Krištof Bozovičar; Tímea Imre; György G. Ferenczy; Stanislav Gobec; György M. Keserű (Taylor & Francis Group, 2024)
AbstractPenicillin-binding proteins (PBPs) contribute to bacterial cell wall biosynthesis and are targets of antibacterial agents. Here, we investigated PBP1b inhibition by boronic acid derivatives. Chemical starting points were identified by structure-based virtual screening and aliphatic boronic acids were selected for further investigations. Structure-activity relationship studies focusing on the branching of the boron-connecting carbon and quantum mechanical/molecular mechanical simulations showed that reaction barrier free energies are compatible with fast reversible covalent binding and small or missing reaction free energies limit the inhibitory activity of the investigated boronic acid derivatives. Therefore, covalent labelling of the lysine residue of the catalytic dyad was also investigated. Compounds with a carbonyl warhead and an appropriately positioned boronic acid moiety were shown to inhibit and covalently label PBP1b. Reversible covalent labelling of the catalytic lysine by imine formation and the stabilisation of the imine by dative N-B bond is a new strategy for PBP1b inhibition.